Identification of extended spectrum beta lactamases, AmpC and carbapenemase production among isolates of Escherichia coli in North Indian tertiary care centre - Uma Chaudhary (Thieme Medical and Scientific Publishers Pvt. Ltd., 2018)
Introduction: Identification of Extended spectrum beta lactamases (ESBL), AmpC production and carbapenemase production among isolates of Escherichia coli, helps clinician to rationalize the choice of antibiotics. However, there is a lack of simple and effective method for simultaneous identification of these beta lactamases.Aim: To determine the concurrent production of beta lactamases using twelve disc method on E. coli isolates.Materials and Methods: A total of 200 multidrug resistant E. coli were screened using twelve disc method. The isolates of ESBL were confirmed by ceftazidime/clavulanic acid and cefotaxime/clavulanic acid method. Metallo-beta-lactamases (MBL) were confirmed by imipenem EDTA combined disc method.Results: Among the 200 isolates, 42.5% were ESBL producers, 9% were MBL and 6.5% were Klebsiella pneumoniae carbapenemase (KPC) and AmpC each respectively. Coproduction was seen in 54 (27%). A significant difference in sensitivity was seen in cefuroxime, aztreonam, cefoxitin and ceftriaxone among inpatient and outpatients.Conclusion: The present study highlights burden of ESBL, AmpC, KPC and MBL along with their coproduction in a tertiary care hospital. In-house antibiotic policy, infection control and epidemiological surveys will help us in controlling these resistant bugs. We believe, the twelve disc method is a simple, inexpensive screening method for beta lactamase production.